Comprehensive Review on the Opportunities and Challenges in the Development of the China’s New Energy Industry in Indonesia - Tangfiyan Tangfiyan (Journal of Comprehensive Science (JCS), 2024)
With the development of sustainable energy industry worldwide, the immense scale of global sustainability challenges requires more than piecemeal solutions from individual country. In general, sustainable development is considered a sign of a country that is moving forward, both in social, economic and political structures. The new energy industry, as the core of global energy development, has become the focus of core business development in the post-epidemic era. Comparing the situation between the government of China and Indonesia, both countries have implemented relevant policies and measures to actively promote the development of new energy industries. Based on the limitations of the current research on the development of the new energy industry in Indonesia and China, this research aims to look at the sustainable development that Indonesia has carried out and also explore in depth the market environment and national conditions of the Indonesian new energy industry, analyze opportunities and risks, and assess the development prospects and challenges of China’s new energy industry in the Indonesian market. This research was prepared using qualitative research methods, namely a data source approach in the form of secondary data from literature and descriptive analysis. Through this method, it is hoped that we can dissect the phenomenon being studied. This qualitative research only describes and explains findings in the field without requiring a hypothesis. This method also raises facts, circumstances, variables and phenomena that occur during research and presents the data as it is. First, Indonesia is a country that has the largest nickel ore reserves in the world. Around 32.7% of global nickel ore reserves are in Indonesia, namely 21 billion tons. Second, nickel is widely used in various industries, including the defense industry. Apart from stainless steel, nickel is also the main ingredient in lithium batteries, which are the main component of electric cars, so it can be said that almost all electronic equipment requires batteries. Thus, the nickel downstream program is an opportunity to transform sustainable national economic development, as well as a ticket for Indonesia to becoming a developed country. This research would bring some reference data analysis and viewpoint support for the development of the China’s new energy industry in Indonesia.